Antioxidants in flour of the oilseed crop Camelina sativa (L.) Crantz - Roberto Russo; Remo Reggiani (International Journal of Plant Biology, 2018)
Forty-seven accessions of Camelina sativa (L.) Crants (41 spring and 6 winter forms) were analyzed for antioxidant activity, total phenolic content (TPC), flavonoids and proanthocyanidins. The antioxidant activity (AA%) was high in camelina accessions and with a significant variability among accessions and between spring and winter forms. The highest antioxidant activities have been observed in some spring accessions (CAM35, CAM173 and CAM268). TPC was high in camelina and significantly different among accessions. Antioxidant activity resulted highly correlated with TPC, while no correlation was observed with flavonoid and proanthocyanidin contents. Significant variability was observed among accessions but not between groups (winter and spring) for flavonoid and proanthocyanidin contents. These two classes of compounds showed a significant inverse correlation between them suggesting that their synthesis is in competition. The camelina cake can enrich the animal diet of antioxidant compounds (phenolics) and some spring accessions are more promising for future breeding programs.